KONTRIBUSI PENDAPATAN USAHATANI PADI SAWAH, ITIK PETELUR, DAN IKAN AIR TAWAR TERHADAP PENDAPATAN TOTAL USAHATANI DI KABUPATEN LEBONG - Prasetyo, Satria Ageng; Romdon, M Mustopa; Badrudin, Redy (Jurnal AGRISEP, 2016)
The paddy farming system in Amen village has experienced multicropping system among paddy, laying duck and fish. This system has economic implication to increasing faming total income. This research aims to analyze the income contribution of each farm commodity on total farm income in village Garut, Amen Subregency, Lebong regency. The method of analysis income contribution was non-cash contribution. The result showed that the contribution of each business was paddy 46 percent, duck cultivation 30 percent, and fishery 24 percent of total farm income.